Interaction of Dihydrocitrinone with Native and Chemically Modified Cyclodextrins - Zelma Faisal; Sándor Kunsági-Máté; Beáta Lemli; Lajos Szente; Dominik Bergmann; Hans-Ulrich Humpf; Miklós Poór (Molecules, 2019)
Citrinin (CIT) is a nephrotoxic mycotoxin produced by Aspergillus, Penicillium, and Monascus genera. It appears as a contaminant in grains, fruits, and spices. After oral exposure to CIT, its major urinary metabolite, dihydrocitrinone (DHC) is formed, which can be detected in human urine and blood samples. Cyclodextrins (CDs) are ring-shaped molecules built up from glucose units. CDs can form host-guest type complexes with several compounds, including mycotoxins. In this study, the complex formation of DHC with native and chemically modified beta- and gamma-cyclodextrins was tested at a wide pH range, employing steady-state fluorescence spectroscopic and modeling studies. The weakly acidic environment favors the formation of DHC-CD complexes. Among the CDs tested, the quaternary-ammonium-γ-cyclodextrin (QAGCD) formed the most stable complexes with DHC. However, the quaternary-ammonium-β-cyclodextrin (QABCD) induced the strongest enhancement in the fluorescence signal of DHC. Our results show that some of the chemically modified CDs are able to form stable complexes with DHC (logK = 3.2–3.4) and the complex formation can produce even a 20-fold increase in the fluorescence signal of DHC. Considering the above-listed observations, CD technology may be a promising tool to increase the sensitivity of the fluorescence detection of DHC.